The last interview - Michelle Burger; Marian Pike (Communicare)
This article pays tribute to Chris Skinner who was a participant in my master’s research entitled “Corporate communication strategy: aligning theory and practice amongst selected public relations practitioners in South Africa.” A man who needs no introduction to the South African public relations industry, Chris Skinner was known as a passionate leader and mentor who left indelible footprints as a lecturer and as the author of the highly influential ‘Public Relations Handbook’. A fellow of the Institute for Public Relations and Communication Management Southern Africa (PRISA); an accredited public relations practitioner and a well respected communication specialist, Skinner had 40 years’ experience in business and corporate affairs (LinkedIn, 2017). During his career he worked, amongst others, as a research associate at the Durban University of Technology (DUT) and as a senior consultant with the East and Southern African Management Institute (ESAMI), and contributed significantly to public relations education, corporate social responsibility, conservation and crisis communication. In addition he served as Chairman of the Wildlife and Environment Society of South Africa (Amanzimtoti) and president of the Amanzimtoti Rotary Club. Skinner died on June 9, 2016. It was only after I learned of his death that I realised this might have been his last interview. I would like to take this opportunity to acknowledge the contribution he made to public relations, and share his comments on corporate communication strategy.